ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME PEMBIAYAAN PERBANKAN SYARIAH DI INDONESIA - Cahyo, Himegah Vivi Tri; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis reseacrh is meant to examine the empirical factors which have influence to the Financing Volume BasedProfit Sharing Which consist of The third party funds, the level of profit sharing, Non Performing Financing,and Total Asset in the Sharia Banking which is listed in Indonesia Stock Exchange. The research type is use thequantitative research. The population of this research is Sharia General Bank and the Sharia Business Unitwhich are listed in Indonesia Stock Exchange (IDX) in 2008-2013 periods. The sample collection technique hasbeen done by using purposive sampling. The samples as many as 168 quarterly financial statements of theSharia Banking. The data analysis method has been done by using multiple linear regressions. Based on the dateanalysis result and the hypothesis test it can be concluded that the variables of Third Party Funds and NonPerforming Financing does not have any influence to the financing volume based profit sharing in the ShariaBanking in Indonesia. Meanwhile, the level of Profit Sharing and the Total Assets have positive influence to thefinancing volume based profit sharing in the Sharia Banking in Indonesia.Keywords: Third Party Funds, The level of Profit Sharing, Non Performing Financing, Total Assets,Financing Volume Based Profit Sharing.